PENETAPAN HARGA JUAL PRODUK (UMKM) DI SUKABUMI DENGAN MENGGUNAKAN METODE COST BASED PRICING - Farijah, Alni Nuraeni; Ramdan, Asep Muhamad; Mulia, Faizal (IAIN Tulungagung, 2018)
Abstrack :The purpose of this research paper is to implement a method of cost-based pricing on CV. Midi Sukabumi in determining the selling price Lidi Osyin Noodle. The analysis technique that used is Â descriptive quantitative approach analysis technique used to analyze numbers using formulas and make descriptions systematically. the result of this research is determining the selling price on CV. Midi Sukabumi by using cost based pricing method are of two calculations, is cost plus pricing used to calculate the total cost of production and non-production process. And the second calculation is the calculation of mark up pricing used for reseller agents by adding a desired mark up on the purchase price of unity.Â Key Words : Full costing, cost based pricing, cost plus pricing, and mark up pricing